Damage protection in fruits: Comparative analysis of the functional morphology of the fruit peels of five Citrus species via quasi-static compression tests - Jentzsch, Maximilian; Badstöber, Marie-Christin; Umlas, Franziska; Speck, Thomas (Frontiers in Materials, 2022)
Due to their special peel tissue, comprising a dense flavedo (exocarp), a less dense albedo (mesocarp), and a thin endocarp, most citrus fruits can withstand the drop from a tree or high shrub (relatively) undamaged. While most citrus fruit peels share this basic morphological setup, they differ in various structural and mechanical properties. This study analyzes how various properties in citrus peels of the pomelo, citron, lemon, grapefruit, and orange affect their compression behavior. We compare the structural and biomechanical properties (e.g., density, stress, Young’s modulus, Poisson’s ratio) of these peels and analyze which properties they share. Therefore, the peels were quasi-statically compressed to 50% compression and analyzed with manual and digital image correlation methods. Furthermore, local deformations were visualized, illustrating the inhomogeneous local strain patterns of the peels. The lateral strain of the peels was characterized by strain ratios and the Poisson’s ratio, which were close to zero or slightly negative for nearly all tested peels. Our findings prove that—despite significant differences in stress, magnitude, distribution, and thickness - the tested peels share a low Poisson’s ratio meaning that the general peel structures of citrus species offer a promising inspiration for the development of energy dissipating cellular structure that can be used for damage protection.